Answer:
Explanation:
We have been given with the quadratic equation
We have general formula to find the roots of a quadratic equation first we find the discriminant with formula
and after that to find the variable suppose x we have the formula
And general quadratic equation is
On comparing the given quadratic equation with genral quadratic equation we will have values
a=1, b=-7 and c=-6
After substituting these values in the formula we will get
After substituting in the formula to find x we will get
The answer is C and D
First we must make one side of the equation zero, so we subtract 7 on both sides of the equation, making the equation 9x^2 - 6x - 6 = 0
Then we will use the quadratic formula to find the answers.
using the Quadratic Formula where:
a = 9, b = -6, and c = -6
and the formula is 6 +-
Essentially, what we need to do here is prove that BE=EC, BE=CB, and.or CE=BC therefore making it isosceles. With ∠AEC=∠DEB, we know AE=DE, so EC=EB (the points go in order). Therefore, as EC=EB, BEC is isosceles (it has at least 2 equal sides).
Feel free to ask further questions!